Health workforce attrition as a governance and implementation capacity challenge: evidence from KwaZulu-Natal, South Africa - Joyce Adefunke Ayeni; Sanjana Brijball Parumasur (BMC Health Services Research, 2026)
Abstract Background Health workforce attrition remains a persistent challenge in public healthcare systems despite formal retention policies. While individual-level explanations - job satisfaction, remuneration, and career opportunities are well documented, less attention has been given to the governance and implementation conditions that shape workforce stability. This study examines health workforce attrition through a governance and implementation capacity lens in the public healthcare sector of KwaZulu-Natal, South Africa. Methods A qualitative descriptive case study design was employed, combining documentary analysis of health workforce policies, strategic plans, annual reports, retention initiatives, and administrative workforce data from KwaZulu-Natal’s public healthcare sector (2011–2018). Data were analysed using a deductive thematic framework informed by health systems governance and policy implementation literature. Workforce indicators - retention rates, turnover rates, staffing levels, and vacancy trends were analysed descriptively to provide contextual insight into workforce stability. Results Documentary analysis of 11 core sources identified four interrelated governance mechanisms associated with workforce instability: (1) retention policy design without adequate operational capacity, (2) fiscal constraints and vacancy management controls, (3) symbolic implementation of workforce reforms, and (4) governance rigidity and constrained managerial discretion. Workforce indicators demonstrated continuing instability during the study period, with patterns broadly consistent with the governance challenges identified. Conclusions Workforce attrition in KwaZulu-Natal’s public healthcare sector is associated with governance and implementation capacity constraints, not only individual-level factors. Strengthening alignment between retention policies, budgetary processes, staffing flexibility, and managerial authority may improve workforce stability though governance reform alone is unlikely to be sufficient where structural competitive disadvantages remain unaddressed. The study contributes to evidence that effective retention requires attention to the organisational capacity needed for implementation, not only policy design. Clinical trial number Not applicable.